Inventory Control Of Raw Materials By Applying The Min-Max Method To Reduce Stockout And Overstock In The Al-Batsit Bakery Home Industry - Nurul Fadilah Ritonga; Hidayat Koto; Firmansyah Firmansyah (CV. Ulil Albab Corp, 2026)
This study analyzes inventory control of raw materials at the Al-Batsit Bakery Home Industry in Bengkulu City using the Min-Max method. The main problem observed was the absence of a systematic inventory control system, leading to both stockout and overstock conditions. This research aims to determine the minimum and maximum inventory levels, analyse the application of the Min-Max Stock method in minimizing storage and ordering costs, and improve the efficiency of raw material inventory control. Primary data were collected through direct observation and interviews with the business owner and production staff. The analysis used the Min-Max method to calculate safety stock, minimum stock, maximum stock, reorder point (ROP), order quantity, ordering frequency, and total inventory cost (TIC). The results show that the Min-Max method produces a total inventory cost of Rp. 6,464,295 per year, compared to Rp. 6,875,550 per year under the current policy, yielding a cost efficiency of (Rp. 411,255 per year). The greatest efficiency was achieved for granulated sugar (12.12%), followed by eggs (5.60%), wheat flour (1.59%), and margarine (0.88%). Implementation of the Min-Max method enables the bakery to establish structured inventory boundaries, prevent stockouts, reduce excess inventory, and optimize ordering frequency without disrupting the production process.